2022
DOI: 10.1152/japplphysiol.00132.2022
|View full text |Cite
|
Sign up to set email alerts
|

Functional optical coherence tomography at altitude: retinal microvascular perfusion and retinal thickness at 3,800 meters

Abstract: Cerebral hypoxia is a serious consequence of several cardiorespiratory illnesses. Measuring the retinal microvasculature at high altitude provides a surrogate for cerebral microvasculature, offering potential insight into cerebral hypoxia in critical illness. Additionally, while sex-specific differences in cardiovascular diseases are strongly supported, few have focused on differences in ocular blood flow. We evaluated the retinal microvasculature in males (n=11) and females (n=7) using functional optical cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Finally, the reduction in area and circumference of the FAZ in the superficial macula was mainly due to an increase in vessel diameter, whereas the decrease in roundness indicated some concomitant vascular distortion. Consistent with previous studies, 24 , 25 , 30 we found increased blood flow density in the retinal macula and parafoveal retinal layers. In particular, although the macular retinal DCP vessel diameter decreased, blood flow density increased because vessel density is defined as the percentage of blood flow pixels out of the total area.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the reduction in area and circumference of the FAZ in the superficial macula was mainly due to an increase in vessel diameter, whereas the decrease in roundness indicated some concomitant vascular distortion. Consistent with previous studies, 24 , 25 , 30 we found increased blood flow density in the retinal macula and parafoveal retinal layers. In particular, although the macular retinal DCP vessel diameter decreased, blood flow density increased because vessel density is defined as the percentage of blood flow pixels out of the total area.…”
Section: Discussionsupporting
confidence: 93%
“…Measurements in 9 healthy individuals (aged 20 – 40 years) who flew for 45 min from 2600 ft to 17 500 ft revealed an 89% flow increase, with concurrent narrowing of the arteriovenous oxygen difference [ 110 ] . Retinal vascular perfusion density was reported to increase after rapid ascent (24 h) from 1130 to 3800 m and was inversely related to partial pressure of arterial oxygen [ 113 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the literature pertaining to choroidal and retinal circulation during flight is scarce, and there is a direct relation between visual function and retinal blood supply [ 145 ] . Future OCT and OCT angiography studies may not only offer knew knowledge about ocular well-being during flight [ 113 ] (of paramount importance for pilots), but may also find applications in a constellation of other serious and debilitating ocular disorders such as diabetic retinopathy [ 146 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The retina has 2 blood supply systems: the central retinal artery supplies the inner layer, and the choroidal blood vessels supply the outer layer. Some studies have shown a correlation between RT and retinal blood flow perfusion, which typically involves retinal vessel density ( 39 , 40 ). The initial observation of an AAV patient’s eye revealed histopathological evidence of inflammatory alterations in the choroidal and retinal vessels, along with media thickening and enlargement of choroidal vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%